MBTI Personality Prediction With Machine Learning - Sonmezoz, Kaan; Ugur, Ozgur; Diri, Banu (IEEE, 2020)
Personality traits, continuously affect our lives, from our behavior to our career decisions. It's possible to design more accurate recommendation systems and develop more efficient digital marketing strategies by the help of personality traits. In this work, people's MBTI personality traits were predicted according to their social media posts. Although it is the first study which uses Turkish language, the results show that personality type prediction can be applied in Turkish language as well. The best results were obtained when the MBTI dimensions were predicted. The F-Score values of those except one dimension are approximately 60%.
Keywords: Natural language processing; machine learning; MBTI; personality prediction; personality traits; BRIGGS TYPE INDICATOR; BIG 5; MODEL; Engineering; Telecommunications